Economic Crisis and Innovativeness – Exploring Geographies of Impact - Fromhold-Eisebith, Martina; Eisebith, Günter (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
The paper explores, mainly from a conceptual angle, regional differences in interdependencies between the recent economic crisis and innovativeness in advanced economies. It addresses two directions of causal relationships between these process fields: In which respects are regional economies more vulnerable or resistant in the face of the crisis, due to their specific constellations of innovativeness? And how does the crisis, in turn, affect regional innovativeness, which may be subject to both hampering and encouraging forces? Arguments that ‘geography matters’ are elaborated by referring to two perspectives, one taking account of regional structure in terms of industry composition, and another one considering region-specific systemic qualities.